2023
DOI: 10.11113/humentech.v2n1.42
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Decision-Making Skills between Athletes and Non-athletes among University Students

Abstract: Cognitive skills are one of the components of mental skills. These skills deal with a high level of cognitive processing, including decision-making. Athletes with high cognitive skills have superior positive thinking and decision-making. The objectives of this study are to evaluate mental skills performance on athletes and non-athletes in university and to investigate the difference of mental skills among athletes and non-athletes in university. 229 active students from Bachelor of Sports Science, Universiti T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although athletes with good cognitive abilities have better positive thinking and decision-making power (Ishak et al, 2023). The result of study by Méndez-Giménez et al (2022) showed that a person's participation in sports has an effect on their EI, sports can improve one's ability to control their emotions, and good emotional regulation techniques have a positive impact on one's EI.…”
Section: Effects Of Soccer Playing On Eimentioning
confidence: 99%
“…Although athletes with good cognitive abilities have better positive thinking and decision-making power (Ishak et al, 2023). The result of study by Méndez-Giménez et al (2022) showed that a person's participation in sports has an effect on their EI, sports can improve one's ability to control their emotions, and good emotional regulation techniques have a positive impact on one's EI.…”
Section: Effects Of Soccer Playing On Eimentioning
confidence: 99%